(untitled) (International Journal of Technology and Management Research, 2020)
This study demonstrates the importance of the Brine Shrimp Bioassay in drug discovery. It uses two medicinal plants, Zanthoxylum xanthoxyloides and Tiliacora funifera. Extracts of Zanthoxylum xanthoxyloides were prepared using water, ethanol, chloroform and diethylether, and each subjected to Brine Shrimp Bioassay. The bioactivities of the extracts were found to be in the order diethylether (LD50=0.958 mg/ml), followed by ethanol (LD50=1.874 mg/ml), water (LD50=2.322 mg/ml), and chloroform (3.518 mg/ml). From Tiliacora funifera is isolated the compound funiferine, which is derivatized to obtain o-methylfuniferine and o-isopropylfuniferine. These were subjected to the brine shrimp bioassay, and the structure –activity relationship (SAR) was determined. The results showed that o-isopropylfuniferine is the most bioactive (LD50 = 9.07 mg/ml), followed by o-methylfuniferine (LD50 =38 mg/ml) with funiferine showing the least activity (LD50 =50.25 mg/ml). The SAR of the compounds indicates that the activity of the compounds increases as the size of the group on the phenolic OH is increased, (i.e. isopropyl (C 3 H7 )> methyl (CH3 ) > hydrogen (H)), which suggests that bulkier groups may give more potent compounds. These two results show that the brine shrimp bioassay can be used as a tool in the search for more bioactive compounds from natural products. Keywords: Brine Shrimp Bioassay, Zanthoxylum xanthoxyloides, Funiferine; o-methylfuniferine,o-isopropylfuniferine.